Axial length, refraction, and retinal vascularization 1 year after ranibizumab or bevacizumab treatment for retinopathy of prematurity - Lin CJ (Dove Medical Press, 2016)
Chun-Ju Lin,1,2 Yi-Yu Tsai1,2 1School of Medicine, College of Medicine, China Medical University, Taichung, Taiwan; 2Department of Ophthalmology, China Medical University Hospital, China Medical University, Taichung, Taiwan Purpose: The purpose of this study was to report on the axial length, refraction, and retinal vascularization 1 year after ranibizumab or bevacizumab treatment for threshold retinopathy of prematurity.Methods: The authors conducted a comparative, consecutive, original study.Results: Twenty-five eyes of 13 patients with threshold retinopathy of prematurity received one intravitreal ranibizumab treatment, and 15 eyes of eight patients received one intravitreal bevacizumab treatment. In the ranibizumab group, the mean gestational age was 26.15±2.08 weeks, with a mean birth weight of 811.15±287.3 g. In the bevacizumab group, the mean gestational age was 26.50±2.14 weeks, with a mean birth weight of 938.38±200.4 g. The mean axial length was 20.34±0.97 mm and the mean spherical equivalent was 0.46±1.36 D in the ranibizumab group, with complete vascularization in 15 of 25 (60%) eyes. The mean axial length was 20.91±1.54 mm and the mean spherical equivalent was -0.60±3.86 D in the bevacizumab group, with complete vascularization in seven of 15 (46.7%) eyes.Conclusion: There were no significant differences in the axial length and refraction between children with threshold retinopathy of prematurity who received intravitreal bevacizumab compared to those who received ranibizumab after 1 year of follow-up. It appeared that the ranibizumab treatment could achieve more complete retinal vascularization than the bevacizumab treatment; however, there was no statistical significance and long-term follow-up is needed. Keywords: bevacizumab, ranibizumab, refraction, retinal vascularization, retinopathy of prematurity, axial length